Different motivations for knowledge sharing and hiding: The role of motivating work design - Gagné, Marylène; Tian, Amy Wei; Soo, C.; Zhang, B.; Ho, K.S.B.; Hosszu, Katrina (2019)
© 2019 John Wiley & Sons, Ltd.